Loss evaluation and performance modelling of power electronics for fault management and renewable energy integration - Ioannou, Stelios; Polycarpou, Alexis; Christofides, Nicholas; Chrysostomou, Michael; Darwish, Mohamed; Marouchos, Christos C. (Frontiers in Electronics, 2025)
This work presents the performance and efficiency analysis of solid-state power electronic devices in two complementary applications: fault current limiting and renewable energy integration. A solid-state Fault Current Limiting and Interrupting Device (FCLID) based on a Switched Capacitor (SC) circuit is evaluated for its ability to perform power factor correction and voltage regulation during normal grid operation. Particular focus is given to switching losses in semiconductors, analysed using the PSIM Thermal Module. The 90° phase shift observed between current and voltage in SC circuits is contrasted with in-phase behaviour in DC-DC converters. IGBT losses are calculated and shown to closely align with simulation and literature-based estimates. The second part of the study investigates a grid-connected photovoltaic (PV) system with power smoothing capability, designed to mitigate output fluctuations due to environmental variability. A bidirectional DC-DC converter and a partially controlled lithium-ion battery are used to reduce voltage flicker and improve grid stability. PSIM simulations incorporate MPPT control, inverter modelling, and real-world component characteristics. Losses are primarily concentrated in switching transistors, diodes, and inductors. Across both systems, efficiency is critically evaluated as a primary determinant of performance and economic viability. The simulated and analytical loss results show agreement within 1%, thereby validating the modelling approach. The findings indicate that lower switching frequencies consistently yield overall system efficiencies above 96%, irrespective of whether MOSFETs or IGBTs are employed. However, the study also reveals that reverse recovery losses become negligible compared to conduction losses only at low switching frequencies (<10 kHz) and low current slew rates (di/dt < 100 A/µs). Finally, the analysis demonstrates that practical implementation factors can increase total power losses by up to 21%.